Diseases of the pancreas (Review of the Seventeenth Russian Gastroenterological Week proceedings, October, 10–12, 2011, Moscow) - I. V. Mayev; Yu. A. Kucheryavyy; A. N. Kazyulin (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
The aim of review. To analyze proceedings of the Seventeenth Russian Gastroenterological Week (October, 10–12, 2011, Moscow), published in the section «Pancreas» (Ros. zhurn. gastroenterol. gepatol. koloproktol. – 2011. – Vol. 21, N 5. – Suppl. 38).Original positions. Analysis of 53 abstracts, accepted for publication as proceedings of the Seventeenth Russian Gastroenterological Week was carried out. The most of publications (64,2%) was devoted to issues of management of patients with acute and chronic pancreatitis (case presentation, surgical, endoscopic and conservative treatment). Overall in 37,7% of abstracts accepted for publication results of statistical analysis were presented. Other publications, some of which invoked major interest, unfortunately, still remain to be only descriptive works and experts opinions.Conclusion. It is necessary to improve quality of the theses presented by authors, first of all by compliance with requirements for publication and presentation of statistical analysis results.